Approximate approach for design of reinforced concrete elevated water tanks on annular shafts against blast loading - Chowdhury, Pronoy Roy (Journal of Structural Engineering, 2024)
Elevated water tanks are important structures and are integral parts of municipal water supply projects. Such structures should be designed against exigencies such as terrorist attack with incendiary bombs and high explosives. Explosion with high explosives causes impulse loading on structures. In this paper, an attempt is made to model an elevated water tank as a SDOF system subjected to triangular impulse loading due to blast. The susceptibility of the R.C shaft staging towards buckling due to blast load is also studied.